Online Journalism The Essential Guide - Hill, Steve; Hill, Steve; Lashmar, Paul (SAGE Publications, 2013)
"An essential guide for anyone hungry to learn how journalism should be practised today, and will be tomorrow. Hill and Lashmar encapsulate the transformative impact technology is having on journalism, but anchor those changes in the basic principles of reporting." - Paul Lewis, The Guardian "As the news business transforms, Online Journalism is a fantastic new resource for both students and lecturers. Informative, straightforward and easily digested, it$1 (Bs a one-stop shop for the skills, knowledge, principles and mindset required for journalistic success in the digital age." - Mary Braid, Kingston University Online and social media have become indispensible tools for journalists, but you still have to know how to find and tell a great story. To be a journalist today, you must have not only the practical skills to work with new technologies, but also the understanding of how and why journalism has changed. Combining theory and practice, Online Journalism: The Essential Guide will take you through the classic skills of investigating, writing and reporting as you master the new environments of mobile, on-demand, social, participatory and entrepreneurial journalism. You will also develop must-have skills in app development for smartphones and tablets, as well as techniques in podcast, blog and news website production. What this book does for you: Tips and advice from leading industry experts in their own words QR codes throughout the book to take you straight to multimedia links A fully up-to-date companion website loaded with teaching resources, detailed careers advice and industry insights (http://onlinejournalismguide.com/) Exercises to help you hone your skills Top five guided reading list for each topic, so you can take it further Perfect for students throughout a journalism course, this is your essential guide!s